A Quality Initiative to Decrease Time Until Analgesic for Fracture-associated Pain in the Pediatric Emergency Department. Issue 5 (September 2021) - Davis, Justin; Kappler, Kristin; Stoker, Skye
Abstract : Introduction: Long bone fractures are a common cause of pain in the pediatric emergency department (PED), and ensuring timely delivery of analgesic medications is essential for these children. We aimed to decrease the median time to the first dose of analgesic for long bone fracture–associated pain in our PED to 36 minutes or less by July 1, 2015. Methods: A series of 4 initiatives were implemented in successive "plan, do, study, act" rapid cycles. Initiatives consisted of educational interventions for staff regarding Emergency Severity Index procedures for triaging pain, transition to in-room triage, enhanced communication about quality goals using a "quality board, " and ongoing staff educational sessions on outlier cases as well as biases and barriers to quality. Results: We implemented the initiatives from April through July of 2015. The monthly median time to analgesic delivery for long bone fracture–associated pain in the PED decreased from 72 minutes in April to 33.5 minutes in July of 2015. For 12 months following the first intervention, the average monthly median time to the first analgesic dose was 48.5 versus 66.3 minutes for the prior 12 months. Conclusions: A series of 4 interventions led to a decrease in the median time to the first dose of analgesic for long bone fracture–associated pain in the PED.